Facility- and Service-based Competition and Investment in Fixed Broadband Networks: Lessons from a Decade of Access Regulations in the European Union Member States - Wolfgang Briglauer; Klaus Gugler; Adhurim Haxhimusa (International Telecommunications Society (ITS), 2015)
This paper employs firm-level panel data of 57 incumbent and entrant firms for 23 European countries in the decade from 2003 to 2012. We examine the impact of service- and facility-based competition on firm level investment as well as the strategic effects underlying infrastructure investment decisions. At the same time we explicitly model the structural dynamics of broadband investment using dynamic panel estimation techniques. We find that facility-based competition exerts a positive and significant impact on both incumbents and entrants implying that incumbents' and entrants' investment decisions are strategic complements. Moreover, this strategic complementarity is much more pronounced with respect to the entrants. Finally, we show that service-based competition appears to have no significant impact on the investment decision of incumbents and entrants and that there is no supportive evidence for the so-called “ladder of investment” hypothesis. With respect to the later phase of market regulation, service-based competition exerts a negative impact on entrants' investment.
Keywords: L43; L52; L96; 330